The Impact Of Health Card On Citizens’ Quality Of Life: Evidence In Bangladesh - Hoque, Md. Rakibul; Uddin, Ramiz; Khan, Mohammad Mostafizur Rahman; Shumi, Farzana Rahman; Sarwar, Fahmida (European Scientific Journal, ESJ, 2016)
People living in the rural areas in developing countries are deprived of the basic needs including health. In Bangladesh, the rural poor people are facing difficulties to be facilitated from the enhanced medical services, mostly because of the increased medical expenses, and the time required to complete the whole process. Henceforth, it is necessary for the government to enhance the medical facilities to its rural citizens for proper development. It has been argued that the health card service system in Bangladesh can enhance the medical services. However, no studies have been conducted to investigate the impact of health card on the quality of life of rural people in Bangladesh. This study attempts to investigate this issue from actual beneficiary perspective. The main objective of this study is to provide a synopsis of the roles of health card on rural citizen of Bangladesh. The data were collected through telephone and face to face interview from a purposive sample in rural community, Bangladesh. The findings show that by using health card service system, rural poor people can get the facilities to visit the doctor directly whereas previously they had to buy ticket and wait for a long time in front of the doctors’ room. The result of this study suggests that, by using health card the quality of medical service can be enhanced as well as the time, cost and number of visit can be minimized. The findings of this research will be very useful for policy maker in Bangladesh.